Optimization of Wear Parameters for Grey Cast Iron under Different Conditions using Grey Relational Analysis. (2018) - Ananth, S.; Udaya Prakash, J.; Moorthy, T.V.; Hariharan, P.
Abstract: The tribological properties such as specific wear rate and coefficient of friction are the major criteria in reciprocating engine mechanism. In this research, two sets of sliding wear tests were conducted based on the Taguchi L27 orthogonal array (OA) and their results were analyzed using grey relational analysis. Load, sliding speed, sliding distance and their different environmental conditions such as different temperatures and different lubricants (T0, T1, T2, L0, L1 & L2) were considered to be the design parameters. Finally optimum parameters for minimum SWR and COF are determined using Grey Relational Analysis. Analysis of Variance (ANOVA) was used to find the percentage contribution of the parameters and that of their interactions. The wear mechanisms of the worn discs were analyzed using SEM micrographs. It has been concluded that the 300⁰C temperature is the best and 15W20 lubricant is the best among the temperature and lubrication conditions respectively.